Den Mund zum Reden in Gleichnissen öffnen: die atomistische Rezeption von Ps 78,2 in Mt 13,35 in ihrer Bedeutung für die Gleichnisrede und die Psalmenrezeption im Matthäusevangelium - Euler, Alida C. (Biblische Zeitschrift, 2023)
The Psalms are an important source for the intertextual grid that underlies the Gospel of Matthew. Particularly, Matthew refers to them in several key passages throughout his gospel (e.g. Ps 91:11f. in Mt 4:6; Ps 110:1 in Mt 22:44; 26:64, Ps 69:22 in Mt 27:34.48; Ps 22 in Mt 27:35.39.43.46). Within the Parable Discourse (Mt 13:1–52) Matthew quotes Ps 78:2 as a ‘fulfillment quotation’ (Mt 13:35). After concluding that most likely the wording of Mt 13:35 does not contain a specification of καταβολή, Matthew’s source for this intertextual reference is determined to be ‘the’ Septuagint, which he changes in the second part of the quotation due to interpretational reasons. Within its closer context this reference to Ps 78:2 serves Matthew to differentiate between the crowds who merely hear what was hidden and the disciples who both hear and understand. For this purpose, Matthew has to refer to Ps 78:2 in an atomistic way. This proves that Matthew is in principle willing to atomisticaly use a psalm, which in turn is important for the discussion of the use of other psalms within the gospel – especially on the extensive use of Ps 22 within the Matthean crucifixion scene.